Perception of Digital Technology in Project Based Learning for Digital Native Students in Elementary School - Nugroho, Bayu Sapto; Rosyadi, Muhammad Irfan; Setyorini, Wulan Fajar; Fauziati, Endang; Sumardjoko, Bambang (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: Education in the digital era is undergoing a significant transformation that demands a paradigm shift in the learning process. Through this learning activity, technology is required to develop students' skills. In this context, an innovative learning approach is Project-Based Learning. Where digital native students are accustomed to using digital technology, they use this technology in their daily lives. Aim: Therefore, the researcher in this study aims to analyse the perception of digital technology in Project-Based Learning for digital native students in elementary schools. Method: This research uses a qualitative approach. Research participants are principals and teachers. Data collection techniques are observation, interview and documentation. The analysis technique used is interactive data analysis through data reduction, data presentation, and data conclusion. Results and Discussions: The results showed that the perception of digital technology in Project Based Learning is the ease of access and use of technology, motivation and involvement in learning, collaboration and social learning, creativity and innovation, and improving technology skills. Conclusion: Through learning activities with project-based learning, students can access various applications and software such as tiktok, zoom, google meet, and learning platforms. Therefore, project-based learning with digital technology has an impact on students in developing varied, innovative, creative and interesting project skills.